Вы находитесь на странице: 1из 37

# .., .., .., ..

2003

4
. , . ,
.

.

- ,
.

1. : ... 3
2. ..... 9
3. 13
4. 16
5. ,
21
6. . 25
7.
.. 29
8. . 32

1. : .
1. P ,
L :
:
P:
"+" : L L L
" P " : P L L
( a , b) a + b
( , a ) P a
:

1.
2.
3.
4.

## < L,+ > - 0 ( ), ..:

+ -
0 L : a L a + 0 = 0 + a
a L a L : a + ( a ) = ( a ) + a = 0
+ .

5.
6.
7.
8.

P :
a L 1 a = a, 1 P.
( a ) = ( ) a , P, a A ( )
( + ) a = a + a , P, a A
(
( a + b) = a + b P, a, b A
)

I.

II.

L .
1 8 .
: 3 , n P,
2
P, C [ a ,b ] , L[ a ,b ] .
.
a1 ,..., a k L,

1 ,..., k P

2. 1 a1 + ... + k a k L .
3. a1 ,..., a k L ,
1 a1 + ... + k a k = 0 1 = ... = k = 0. (0 P).
a1 ,..., a k L , 1 ,..., k P ,
, , 1 a1 + ... + k a k = 0 .

1.
.
( !).
2. a1 ,..., a k (
) b1 ,..., bl , b1 ,..., bl
c1 ,..., c m , a1 ,..., a k
1 ,..., c m .
def

4.
.
def
.
.
5. M L
, x L a1 ,..., a k M , 1 ,..., k P : x = 1 a1 + ... + k a k .
3. M a M : a
M \ {a} , M \ {a} .
. x L M, M
2
M \ {a} x M \ {a}
M \ {a} - L.
.
6. L
L.
7. ( def) L max
L.
def 6-7.
1

- def 6, x L x = {x}
A max L.
def 4
def 7, x L A {x} -
a1 ,..., a k , x (x
) 1 ,..., k P,
= 0 : 1 a1 + ... + k a k + x = 0 .
4

, 0 ( a1 ,..., a k - )
1
x = ( 1 a1 + ... + k a k ) A - L

def 6.
. L { 0}
.
. ( , ..
).
. < A, >
: - ,
b A : c B c b, .. . a A
a A : a a . (def max - a : a a
a A , a = a ).
A = { A1 ,..., Ak ,...} -
L. L {0} a L : a 0 {a} - A .
def

: A j Ak A j Ak . , < A, >
.
B A B . , A A : B B
def

B A. , A = B. , A A, .. A
BB

.
: , a1 ,..., a k A, ,
B Bi1 ,..., Bik : a1 Bi1 ,..., a k Bik .
a1 ,..., a k - . A = B
B
B Bi1 ,..., Bik , ,
Bim B a1 ,..., a k Bim . ,
Bim a1 ,..., a k - .
, A A B B B A - .
max L.
. ,
max - L.
:
. ( ) a1 ,..., a m
L L.
5

. a1 ,..., a m ,
:
a1 a1 = 0 , a1 , a 2 ,..., a m ; a1 0 ;
a 2 , a 2 a1 ,
a1, a 2 ,..., a m - 3;
a 3 , a 3 a1 a 2 ..
m ( 3) a1 ,..., a n . ,
, .. L. : a1 ,..., a n
1 ,..., n P, = 0 : 1 a1 + ... + k a k = 0 . k 0,
1
( 1 a1 + ... + k 1 a k 1 ) -
k +1 = ... = n = 0. a k =
k
a1 ,..., a n . ,
a1 ,..., a n - - L.
a1 ,...,a n L.
1. x L .
. 6: .
2. 1 x L 1 ,..., n P : x = 1 a1 + ... + n a n . 1 ,..., n
x .
.
. x = 1 a1 + ... + n a n = 1 a1 + ... + n a n ,
0 = ( 1 1 )a1 + ... + ( n n )a n

a1 ,..., a n . .

i i = 0 i = 1,..., n i = i i = 1,..., n.

8. L ,
.
.
L {0}
.
. L
a1 ,..., a n .

x1 , x 2 ,..., x m ,...
-

(1)
(2)

L ( ). , (2)
n.

1- .
x1 , a1 ,..., a n

(3)

- , 1 ,..., n P, = 0:
x1 + 1 a1 + ... + n a n = 0 .
x1 0, .. x1 (2). 0 - a1 ,..., a n - .
i 0 a i (3). a i
(3),
x1 , a1 ,..., a n 1
(4)
(4) - ( 3).
2- .

x 2 , x1 , a1 ,..., a n 1

(5)

, .. x 2
(4). x 2 , x1 -
a1 ,..., a n 1 (5).
(5),
x 2 , x1 , a1,..., a n 2

(6)

3- .
(6) x 3 ..
(2) n , n
x n , x n 1 ,..., x 2 , x1 .

(7)

## (7) (2) (7) L. m > n : x n +1 (7) L,

x n +1 , x n , x n 1 ,..., x 2 , x1 .
, (2) m n.
(1) (2) . n m n = m.

def
9. L dim L = L.
def

dim{0} = 0.

dim L P :

. P
.

2. .
< a1 ,..., a k >
a1 ,..., a k L P.
def

## < a1 ,..., a k > = min L, a1 ,..., a k .

, < a1 ,..., a k > = { 1 a1 + ... + k a k | 1 ,..., k P} -
a1 ,..., a k a1 ,..., a k -
< a1 ,..., a k > .
dim < a1 ,..., a k > = max a1 ,..., a k .
< a1 ,..., a k > - max
a1 ,..., a k .

A = ( a ij ), 1 i m, 1 j n, a ij P - m n
P.
Ai = ( a i1 ,..., a in ) i - A, Ai Lnc - n P.
a1 j

.
A j = . - j A, A j Lmc - m P.

.
a
mj
def

def

## Lmc V = < A1 , A 2 ,..., A n > - .

: , dim V = dim V , r = r .

def

dim V = r max A = .

def

dim V = r max A = .
() .
. A , :
1: As = At , At = As , Ai = Ai i s, t ( s t).
2: As = As + At , s t , Ai = Ai i s, P.
( ).

( ).
A ,
1. r ( A) = r ( )
2. r ( ) = r ( ).
1. 2. , .
1

. V ( A) = < A1 ,..., As ,..., At ,..., Am > = < A1 ,..., At ,... As ,..., Am > = V ( A)
1. dim V ( ) = V ( ),
r ( ) = r ( ).
2

## . As = As + At . V ( ) = < A1 ,..., As + At ,..., At ,... Am > =

= < A1 ,..., As ,..., At ,..., Am > = V ( ) r ( ) = r ( ).
n

2.

A
j =1

x j = 0 .

0

.
n
n
j
j
, A j = 0 A j = 0, 0 = . . max

j =1
j =1
.
0

max
. r ( ) = r ( ).
. max
def

= max = rgA. - .
. , r ( ) = 0, r ( ) = 0 - .
. ( )
:
0 ... 0 a1i

0 ... 0 0
0 ... 0 0

.
. . .

A= 0 . .
.

.
0 . .
0 . .
.

. . .
.

.
0 . .

... a 1k
... a 2 k
... 0
.
.
.
.
.
.
.
.
.
.
.
.
Ai

Ak

... a1l
... a 2 l
... a 3l
.
.
.
.
.
.
.
.
.
.
.
.

... a 1 p
... a 2 p
... a 3 p
.
.
. a r 1, p
.
0
.
.
.
.
.
.

Al

Ap
10

... a1n A1

... a 2 n A2
... a 3n A3

.
.
... a r 1,n Ar 1

... a rn Ar
.
0
.
.

.
0
As
An

... a 1s
... a 2 s
... a 3s
.
.
... a r 1, s
... a rs
.
.
.
.
.
.

## 1 i < k < l < ... < p < s n,

a1i a 2 k a 3l ... a r 1, p a rs 0.
r ( ) = r ( ), r ( ) = r ( ), ,
r ( ) = r ( ).
A1 ,..., Ar r ( ) = r.
A i,k,l,,p,s ,
A ,

A i x1 + A k x 2 + A l x 3 + ... + A p x r 1 + A s x r = A ,
( A i , A k , A l ,..., A p , A s ) .
A i , A k , A l ,..., A p , A s r,
A ,
. r ( ) = r = r ( ).

. - max
.
. rgA =
.
n

j =1

xj = B

rgA = rgA | B.
.
. , 1 ,..., n P :

A
j =1

= B

A rgA | B = rgA.
. rgA | B = rgA. ( rgA =
= rgA+1) 1 ,..., n P :

A
j =1

= B 1 ,..., n - .

. rgA = , 0.
. , ,
0 0.
rgA=r. r ,
r A i , A k , ,..., A s
a1i a 2 k a 3l ... a r 1, p a rs 0, > r ,
, 0. .
11

, max , 0,
r=rgA.
. n detA = 0 ()
rgA = r < n.
.

det A .

det A = 0

rgA < n.
rgA< n n (detA) 0 detA =0.

12

3. .
Ln - P
: Ln Ln - (..).
1. x 0 ..
P, x = x.
..
e : e1 ,..., e n - Ln , .. e,
x1

.
[ x ] = . - x e. x = x ( )

.
x
n
0

.
A[ x ] E [ x ] = [ 0 ], , [ 0 ] = . ,

.
0

A[ x ] = [ x ],

( E A)[ x ] = [ 0 ]

( )

- n n x1 ,..., x n
.
1 x 0,
( ). () det( E A) = 0, ..,
det( A E ) 0, () .
def

f ( ) = det( E A) - n
( .. ), () [x]
f ( ) = 0 P, .. - .. ,
P.
1 ,..., k - f ( ), P.
1 (). () = 1 -
.. .
() 2 ,..., k = 1
.. 1 ,..., k .

13

. P - , f ( ) P ,
, (
). ..
. P , f ( )
P (: E 2 ).
.
Ln , .. ?
: .. :
Aj

j
. . .

def

= [ e j ]

- e j e.

1 ( ..
).
.. : Ln Ln e A = diag ( 1 ,..., n )
e .. , 1 ,..., n .. .
.
. e : e1 ,..., e n ..
0 0
1

. .
1

1 = i =

i
=
1
,...,
n
[

e
]
=

i
i
.

0 0
A=
.

. .

0 0

= [ei ] e
= i [ei ], .. ei = i ei i e ..
1 ,..., n .
. e : e1 ,..., e n ..
1 ,..., n , i = 1,..., n ei = i ei e
i

, .. .
A=
.

14

. . Ln ,
.. .
Ln , .. ?
. .. ,
, .
. s1 , s 2 ,..., s k -
1 , 2 ,..., k , i j i j.
k.
k = 1 s1 - , .. s1 0 .
s1 ,..., s k 1 . ,
s1 ,..., s k 1 , s k .

(1) 1 s1 + ... + k 1 s k 1 + k s k = 0 - ( i P )

1 1 s1 + ... + k 1 k 1 s k 1 + k k s k = 0, .. s i = i s i i = 1,..., k .
(1) k (2):
(2)

1 ( 1 ) s1 + ... + k 1 ( k k 1 ) s k 1 = 0 . s1 ,..., s k 1 - ,
0
0
1 ( k 1 ) = ... = k 1 ( k k 1 ) = 0 1 = ... = k 1 = 0. (1)
s 0

k
k s k = 0 k = 0. , (1) 1 ,..., k 0
s1 ,..., s k .

2 ( ..
).
f ( ) .. : Ln Ln , Ln P,
P n (.. P ), Ln
, .
. , Ln n
(!) , Ln
. 1 .
. , :
= id : Ln Ln 1, Ln
.. = id .

4. .
15

: Ln Ln - .., Ln P - .
1. x Ln h ( h N)
h
h 1
0 .. , ( 0 ) x = 0, ( 0 ) x 0,

= id : Ln Ln . 0 0,
.. . 1.
1. 0
n
N 0 L . N 0
0 .
n
h
2. N 0 = {x L | ( 0 ) x = 0}, h 0
.. .

3. ,
.. , .
Ln .
4. 1 ,..., k - () ..
: Ln Ln .
Ln = N 1 + ... + N i + ... + N k
(*)
1

- ( ) ,
N i = {x Ln | ( i ) hi x = 0}, i = 1,..., k .
. .. ..:
= 1 + ... + k , i = | N i , i = 1,..., k .
.. i : N i N i i .
..
i , i .

- .. .
16

: .
1. L - Ln P.
a1 ,..., a l L L,
n

a
i =1

a
i =1

def

L i = 0 ( i P ),

L ( 1 ,..., l ) (0,...,0).

L = {0}.
2. Ln L - e1 ,..., e m Ln ,
L Ln .
. L
L L.
n

.. : Ln Ln ( Ln P - )
0 P. f ( ) ..
f ( ) = ( 0 ) n

n
( 0 ) n = 0 - x L

( 0 ) n x = 0 Ln - .
k
g ( ) .. f ( ) g ( ) = ( 0 ) , k n,
Ln

k.
def

.. : Ln Ln , = 0 .
g ( ) , k = 0, k 1 0.
, :
1. :
L L .
, x L
x L ( 0 ) x L x L + 0 x = L x L.
L

2. 0
0 .
, x = y ( 0 ) y = y y = ( + 0 ) y (
0 ) + 0 = 0 = 0.
(i = 0,,k)
def
N = {x Ln | i x = 0} - i.
i

i N i - .
:
17

## {0} = N 0 N 1 ... N i 1 N i ... N k 1 N k = Ln , (, ?)

N i N i 1 N i

(1)
(2)

Ln (, ).
e1 ,.., e r - N k N k 1 . (2) e1 ,..., e r N k 1 . ,
e1 ,..., e r - N k 2 . 1 ,..., r P = 0, ,
( 2)

## 1 e1 + ... + r e r N k 2 , ( e + ... + e ) N e + ... + e N

1 1
r r
k 2
1 1
r r
k 1
N
e1 ,..., e r k 1 - .
N k 2 e1 ,..., e r N k 1
N k 2 :
e1 ,..., e r , f 1 ,..., f s - N k 1 N k 2 .

(2)
N k 3 ,
2 e ,..., 2 e , f ,..., f N
1

k 2

N k 2 N k 3 ..
k-1 ( k = 0) :
N k N k 1
N k 1 N k 2
N k 2 N k 3
( k 2) 2 e1 ,..., 2 e r , f 1 ,..., f s , g 1 ,..., g t
..
..
k 2
k 2
k 3
k 3
k 4
k 4
( 2)
e1 ,..., e r , f 1 ,..., f s , g 1 ,..., g t ,...
N 2 N 1
(k )
e1 ,..., e r
( k 1) e1 ,..., e r , f 1 ,..., f s

(1)

..., h1 ,..., hu

N1

N 0 = {0}

## : (1) N 1 (1) ( 2) - N 2 ... (1) ( 2) ... ( k ) -

N k = Ln .
, :
e1 = k 1 e1 ,

e 2 = k 2 e1 , ..., e k = e1 ,

e k +1 = k 1 e 2 , e k + 2 = k 2 e 2 , ..., e 2 k = e 2 ,
.
e n 1 = hu 1
e n = hu .

## .. < e1 ,..., e k >

18

e1 = k e1 = 0 e1 = 0 e1
e 2 = e1 ( 0 ) e 2 = e1 e 2 = 0 e 2 + e1
.........................................................................
e k = e k 1 ( 0 ) e k = e k 1 e k = 0 e k + e k 1 .
e1 ,..., e k < e1 ,..., e k > |< e ,...,ek
0

1
0

.
.

.
.

.
.

.
0

1
0

>

k.

, (1) ... ( k ), : .. ,
.
.. Ln = ,
( + , .. = {0}) , e1 ,..., e n (- )
(1) ... ( k )
- 0 . - =
(= (1) (k)).
- = . - = k =
= 0 .
. , - .
.
: Ln Ln - .., Ln P
.
f ( ) = ( 1 ) k1 ... ( m ) k m - , i P, i j
i j.
g ( ) = ( 1 ) h1 ... ( m ) hm - , hi k i , i = 1,..., m.

Ln = N 1 + ... + N m
-

(1)

,
N i = {x Ln | ( i ) hi x = 0}.
19

= 1 + ... + m , i = | N i : N i N i .
i i . N i e1i ,..., e ni i (
), i - (-)
i . =
i ( ) i , max
= hi - i min i .
i
i
e1 ,..., e ni , i = 1,..., m. (1) ,
e : e1 ,..., e n Ln . e, .. ,
= 1 ,..., m , ..

def .
. .. , ..
( Ln
, min
(1) ).
(!) : .. : Ln Ln , Ln P -
, Ln ,
.
(!) .
, ,
, .

5. ,
.
: Ln Ln - .. Ln ,
20

: Ln Ln - .., ( x, y ) = ( x, y )
x, y Ln.
e Ln
A = A .
.
1. .. : Ln Ln
, = .
:
A A = A A .
1. a - ..
p, a - p.
. a = pa ( p )a = 0 .
=

0 = ( ( p )a, ( p )a ) = ( ( p ) ( p )a , a ) = (( p )( p )a , a ) =
= (( p )( p )a , a ) = (( p )a , ( p )a ) ( p )a = 0 a = pa.

2. ,
.. , : a = p a , b = r b, p r ab.
.1

. p( a , b) = ( pa , b) = ( a, b) = ( a , b) = ( a , r b) = r ( a , b).
pr

( p r )( a, b) = 0 ab.
..
. : Ln Ln - .. Ln . Ln
,
.

.
1. a1 0 - ( , .. Ln
), a1 = p1 a1 . < a1 > = L1n 1 = {x Ln | ( a1 , x ) = 0} < a1 >
21

1. , L1n 1 -
.1

: x L1n 1 ( a1 , x ) = ( a1 , x ) =
= p1 ( a1 , x ) = 0 , ( a1 , x ) = 0, .. x L1n 1 = <a1 > x L1n 1 , .. ( a1 , x ) = 0.
.., Ln = <a1 > + L1n 1 - ( , ..
L Ln = L + L ).
n 1
2. L1n 1 a 2 | Ln 1 ( L1
1

), | L1n 1 a 2 = p 2 a 2 .
1 ,
n 1
L1 = <a 2 > + Ln2 2 - | L1n 1 ,
Ln2 2 - < a 2 > L1n 1 .
n-1
Ln = <a1 > + < a 2 > + ...+ < a n >,

()

a i - p i , a i a j i j.
() , a1 , a 2 ,..., a n - Ln
. e:
def
1
ei =
a i , i = 1,..., n. .. e , e
ai
.

.
: Ln Ln - .. . Ln
,
1

## + r cos 1 sin 1 + ... + r cos l sin l ,

.
l

1 sin 1 cos 1
sin l
cos l

k + 2l = n,
k l = 0,
1 ,..., k - ,
ri - i i i i -
, i = arg( i + i i ).
.
22

2. .. : Ln Ln ()
(), :
x, y Ln ( x, y ) = ( x, y ).
2 ( x, y ) = ( x, y ) x, y = = 1 .
= = () .. !
.. () .. ,
, ,
..
()
Ln U U = E , U 1 = U
() .
1. ()
.. 1.
.. -
.. . a ..
: a = a , a 0 . - ( a, a ) = ( a, a ) = ( a, a ) =
= ( a, a ) = 1 = 1.
.. : Ln Ln .
Ln ,
1.
..
1.
.. : Ln Ln .
Ln ,
cos m sin m
cos 1 sin 1
+ ... +
,
E k + ( E l ) +
sin 1 cos 1
sin m cos m
k + l + 2m = n

0 k , l n, 0 m

n
.
2

..
1: i = 1 i = +1 - 1,ri = i i i = 1.
(, ) .
23

3. .. : Ln Ln Ln
, = .
3 ( = ) , ..
.
2. ..
.
.. : Ln Ln
Ln .
- .. . Ln a 0 : a = a.
( a, a ) = ( a , a ) = ( a, a )
a0

= R.

( a , a ) = ( a , a ) = ( a, a )
..
.
: Ln Ln - ..
Ln . Ln
,
.
..
2.

6. .
1. F Ln R
-

24

F : Ln Ln C R
( x, y ) F ( x, y ) C R,
:
1. z Ln , x, y Ln , , C ( R)
F ( x + y , z ) = F ( x, z ) + F ( y , z ).
2. x Ln , y , z Ln , , C ( R)
F ( x, y + z ) = F ( x, y ) + F ( x, z ).
,
Ln .
.
x1
y1

y = y j e j , [ x ] = ... , [ y ] = ... .
j =1
x
y
n
n

e : e1 ,..., en L , x = x i ei ,
n

i =1

n
n
n
n

def

F ( x, y ) = f x i ei , y j e j = F ( ei , e j ) x i y j = a ij = f ( ei , e j ) = a ij x i y j =

i , j =1
j =1
i =1
i , j =1
n

i =1

j =1

= a i a ij y j = ().
def

A = ( a ij ) i , j =1,..., n - F e, a = F ( e , e ),
e
ij
i
j
n

y = y j e j - , y,
j =1

y1

[ y ] = ... .
y
n

() F ( x, y ) = [ x ]t A [ y ], t .
e
.
n
e : e1 ,..., e n - L , T = (t ij ) - e e :
n

e j = t ij ei . [ x ] = T [ x ], [ y ] = T [ y ].
i =1

________

F ( x, y ) = [ x ]t A [ y ] = T [ x ] t A ( T [ y ] ) = [ x ] t T t A T [ y ]
e
e
e

A = T t A T = S t A S , S = T - e e : e j = t ij ei .
e
e
e
i =1

25

def

2. rgF = rg A - -
e

L .
, ..
def: rg Ae = rg A
e
.
T t , T rg A
e
3. F - Ln . f : Ln C
def

R, f ( x ) = F ( x, x ) x Ln , ,
F.

, ,
(.. F ( x, y ) = F ( y , x )
x, y Ln ). ( )
def

4. rg f = rg F , ..
.
n
e L

f ( x ) = [ x ] t A [ x ], A - F e.
e
e

A = S t A S - F e .
e
e
5. () f g Ln
, f ~ g , .. : Ln Ln ,
f ( x, y ) = g ( x, y ) x, y Ln - ;
f ( x ) = g ( x )
x Ln - .
- .., f g
.
~ ()
.
? .

.
6. F (),
__________

F ( x, y ) = F ( y , x ) x, y Ln C

( F ( x, y ) = F ( y , x )
26

x, y Ln R ).

f (),
F ().
()
() Ln .
() .
1. ()
():
A = A t
__________ _

a ij = F ( ei , e j ) = F ( ei , e j ) = a ji
A = A t

2. Ln A F
f (), F f - ().
t
. A = A a ij = a ji .

F ( x, y ) =

i , j =1

ij

xi y j =

__________ ____
n

i , j =1

ji

__________

y j x i = F ( y , x ) F - ().

3. F ( x, y ) - f ( x ) = F ( x, x ) R x Ln , ..

.
.
__________
________
. F , F ( x, y ) = F ( y , x ) . f(x) = F(x,x ) = F(x,x) = f ( x ) =
= F ( x ) R x Ln .
. ().
7. () F
a : a1 ,..., a n Ln , x, y Ln
n

x = xi ai , y = y j a j
j =1

i =1

F ( x, y ) = i x i y i , i R.
i =1

( F ( x, y ) = i x i y i .F ).
i =1

() f a
n

n
, x L , x = x i a i
i =1

27

i =1

i =1

f ( x) = i xi xi = i xi

( f ( x ) = i x i2 f), i R.
i =1

.
. F f - ()
() Ln . Ln , F
f .
. A F f
e. A (.) (.) U ,
1

- , ,..., -
U 1 AU =
.
1
n

A, i R , .. A (.).
(.) U, U 1 = U t , U 1 AU = U t AU =
1

,
=
.

A, F f (.. U t AU F f ).
. ,
.
rg f = r < n A 0 n-r.
1

r
, i 0, f
U t AU =
0

f ( x) = i xi
i =1

f,

f ( x ) = i x i2 f.
i =1

7.
.
28

, f ( x ) R f - (.) .

.

1.
2.
3.
4.
5.

1. f Ln
, x Ln f ( x ) 0 f ( x ) = 0 x = 0 .
, x Ln f ( x ) 0 f (x) = 0 x = 0.
,
x Ln f ( x ) 0.
,
x Ln f ( x ) 0.
,
x, y Ln : f ( x ) > 0, f ( y ) < 0.

.
r
2
r

f ( x) = i xi
= i x i2 - . f
i =1
i =1

## 1 ,..., k > 0, k +1 ,..., r < 0. x i = i x i ,

i = 1,..., r, x r +1 = x r +1 ,..., x n = x n , (
1
ei , i = 1,..., r, ei = ei
, .. ; ei =
i
i = r,..., n - ), f
:
2

f ( x ) = x1 + ... + x k

x k +1

... x r

- ;

## f ( x ) = x1 2 + ... + x k 2 x k 2+1 ... x r 2 - .

2. I + = k - f.
I = r k - f.
I + + I = r = rg f
def

s = I + I - f.
.
I + , I ( s ), r = rg f
f, .. , ,
, .
. r def rg f.
I + I . Ln
e : e1 ,..., e n e : e1 ,..., e n , f :
29

f ( x ) = x1

+ ... + x k
2

x k +1
2

... x r ,

(1)

(2)

## e f ( x ) = x1 + ... + x l x l+1 ... x r

l < k.
Ln L = <e1 ,..., e k >, L = <e l+1 ,..., e n > .
dim( L + L ) = dim L + dim L dim( L L )
dim( L L ) = k + ( n l ) dim( L + L ) k l > 0 x 0 0 : x 0 L L .
n

x 0 L x 0 = x e + ... + x e f ( x 0 ) > 0
.

(2)

## x 0 L x 0 = x l0+1 el+1 + ... + x n0 e n f ( x 0 ) 0

0
1 1

0
k k

(1)

, k = l = I + , r k = r l = I .
. 4
: r, I + , I , s, 2 ,
. f g f g
(..
.. ).
f ,
i I + , I !
. .. f
, .
. f Ln :
1. r = I + = n
2. r = I = n
r=I+ <n
3.
r= I <n
4.
I + > 0, I > 0, r > 0.
5.
. 1,3,5, .. f -
() -f - ().
e1 ,..., e n f
f ( x ) = x1

+ ... + x k

x k +1

... x r ,

0 k r, 0 < r n, k = I + , r k = I .
(5). I + > 0, I > 0, x = e1 , y = e k +1 :
f ( x ) > 0, f ( y ) < 0 f - .
30

, f - , I + = 0 ( I = 0 ), x Ln
f ( x ) 0 ( f ( x ) 0) - .
(3;1) f -

I = 0 I + = r.
I + = r = n, f ( x ) = 0 x = 0 f - .
, f , r < n, f ( e n ) = 0 .
. f
f .

.., .. .

8. .
31

1. < G, > -
, :
1. x, y G x ( y z ) = ( x y ) z -
2. e G : x e = e x = x, e -
3. x G x 1 G : x x 1 = x 1 x = e.
2. < G, > , H G. < H , >
< G, >, < H , > .
:
1. x, y H x y H
H
1.

1
2. x H x H
3. e H (
1 2 y = x 1 ),
.. () H () < G, > .
1-3 :
1 . x, y H x y 1 H .
.
( )
< G, > - ,
1. h H

< H , > - .

h H = H , h H = {h x | x H }.

.
.1

1. z h H . x H : z = h x. h, x H h x H z H .
.., h H H .
1 2

2. x H . x = h ( h 1 x ), h, x H h 1 x H , x hH .
.., H h H . , hH = H .
2. , g G g H = H , g H .
, e H g e g H = H g H .
=g

3. H H = H .
1.

: H H = {h x | h, x H } = {h H | h H } ={H | h H } = H .
4. H 1 = H .
.
32

H 1 = {h 1 | h H }
h H

1 1

(h )

.2 .2

=h

H 1 H .
H

H 1 = H .

.
3. < G, > - , < H , > - .
G H g H = {g h | h H }, g -
G. , H g - .
.
.
( )
1. G H , .
. a g 1 H g 2 H . h1 , h2 H : a = g 1 h1 = g 2 h2
g 2 = g 1 h1 h21 g 2 H = g 1 h1 h21 H

g1 H .

2. g G g H . G
G H.
3. G H ,
H.
def

. g G L g : G G, L g x = g x x G
-. L g H = g H Card g H = Card H .
4. G H
G H.
. 1 : G G , x x 1 x G - .
fH gH = ( f H ) 1 ( g H ) 1 = Hf 1 Hg 1 = . 1
= Hf 1 = Hg 1

.
4. ( ( 4)) G
H (G : H) H G.
(G : e) = G.
H = {e}
. G H
33

(G : e) = (G : H ) ( H : e).

()

. 3
( H : e). 1 2 G H
G, (G : H ). ().
5. < H , > < G, >
( H G ), x G x H = H x.
.
.
, H G x G xHx 1 H
).

.
< G, > - , H . G -
G H. G :
def

( x H ) ( y H ) = xy H .
: H G < G, >
:
x H y H = x( H y ) H = x( y H ) H = x y H H = x y H .
, G , ..
x H y H
x H = x H
?
. x y H = x y H .
y H = y H
x x H h1 H : x = x h1
y y H h2 H : y = y h2
H G y H = H y h3 H : h1 y = y h3

x y = x h1 y h2 = x y h3 h 2 x y H x y H = x y H .

, < G , > -
x H , y H , z H G x H ( y H z H ) = x H ( y z H ) = x y z H
. .

1.
(x H y H ) z H = x y H z H

34

= x yzH

2. e = H G :

3. x H G

x H G x H H = x H
H x H = x H.

( x H ) 1 = x 1 H G , ..

(x H) (x-1H ) = x x 1 H = H = e , ( x 1 H ) ( x H ) = x 1 x H = H = e .
, < G , > - , G H.
: G / H .
(G : e ) = (G : H ) =

(G : e )
.
( H : e)

.
4. < G, > < G , > - . f : G G
, x, y G f ( x y ) = fx fy.
f , f - .
G G - .
f : < G , > < G , > ( -).
f e = e.
1. e, e - G G .
1
1
2. x G f ( x ) = ( f x ) .
3. ( )
.
5. Im f = { y G | x G : f x = y} - f.
Kerf = {x G | f x = e } - f.
4. Im f - < G , >,
Kerf - < G, > .
.
I. f : < G , > < G , > - , H = Kerf .
: 1. H G
2. G / H Im f , .. .
II. ,
< G, > - H G, f : G G / H
~
Kerf = H .

35

.
fh = e

I.

1. x G, h H f ( x h x 1 ) = f x f h ( f x ) 1 = e x H x 1 H H G.
2. f : G Im f - ( f).
f : G / H Im f ,
def

gH G / H

f ( gH ) = fg.
f , f
gH :
g 1 g H , g 2 g H , h1 , h2 H : g 1 = gh1 , g 2 = gh 2 i = 1; 2
fg i = f ( g hi ) = fg fhi = fg e = fg.
( ).
f :
?

g 1 h = g 2 H f ( g 1 H ) = f ( g 2 H ).

g 1 g 2 H h H : g 1 = g 2 h fg 1 = f ( g 2 h ) = fg 2
fh = fg 2 ,
=e

f ( g 1 H ) = fg 1 = fg 2 = f ( g 2 H ).

a) f - :
f ( g 1 H g 2 H ) = f ( g 1 g 2 H ) = f ( g 1 g 2 ) = fg 1 fg 2 = f ( g 1 H ) f ( g 2 H ).
( G/H)
b) f - :
f ( g 1 H ) = f ( g 2 H ) fg 1 = fg 2 f ( g 1 g 21 ) = e g 1 g 21 H
g 1 Hg 2 = g 2 H g 1 H = g 2 H .
c) f - :
g Im f g G : fg = g f ( gH ) = g .
b) - c) f -
a) - c) f - .
II.

def
H G. f : G G / H , g G ~
fg = gH .

~
~
, f - (gH G / H g G : fg = gH ).
~
f - : ( < G, > < G / H , > )
~
~
~
f ( g 1 g 2 ) = g 1 g 2 H = g 1 H g 2 H = fg 1 f g 2 .

36

~
~
Kerf . g Kerf , fg = gH = e = H g H ,
~
, Kerf = H .

37

## Нижнее меню

### Получите наши бесплатные приложения

Авторское право © 2021 Scribd Inc.